The Impact of Gas Flaring on Child Health in Nigeria - Alimi, Omoniyi Babatunde (The World Bank, 2022)
Burning off the gas coming out of oil wells-gas flaring-is a common practice in oil-producing developing countries. This economically wasteful and environmentally damaging process occurs because infrastructure has been built with a focus on oil production rather than gas capture and because weak regulations and limited environmental monitoring make flaring an attractive choice for oil producers. Moreover, gas flaring is harmful to human health, especially because of pollutants. This research focuses on Nigeria, where over 10 percent of all gas produced is flared and about 2 million people in the Niger Delta live within four kilometres of a gas flare. While several studies from developed countries examine relationships between gas flaring and human (especially infant) health, a lack of data limits what research is possible in developing countries. This paper uses infant health data from Demographic Health Surveys, and satellite-detected data on gas flaring to examine the effects of flaring on disease incidence and infant mortality in oil-producing regions of Nigeria. The findings show a strong positive association between gas flaring and the incidence of respiratory diseases and fever among children younger than five years. The study contributes to the literature measuring the wider cost to society of oil and gas production and adds to a growing body of work using satellite data to understand well-being in places where conventional data sources are unavailable or unreliable
Keywords: Air Quality and Clean Air; Demographic Health Survey Data; Early Child and Children's Health; Early Childhood Development; Energy; Environment; Environmental Hazard; Environmental Regulation; Gas Flaring; Gas Production Regulation; Hazard Risk Management; Infant and Child Health; Oil and Gas; Oil and Gas Production; Satellite-Detected Health Data; Stunting; Education